2021
DOI: 10.1111/mcn.13260
|View full text |Cite
|
Sign up to set email alerts
|

High levels of breastmilk feeding despite a low rate of exclusive breastfeeding for 6 months in a cohort of vulnerable women in Toronto, Canada

Abstract: Exclusive breastfeeding (EBF) for 6 months is a global public health goal, but measuring its achievement as a marker of population breastmilk feeding practices is insufficient. Additional measures are needed to understand variation in non-EBF practices and inform intervention priorities. We collected infant feeding data prospectively at seven time points to 6 months post-partum from a cohort of vulnerable women (n = 151) registered at two Canada Prenatal Nutrition Program sites in Toronto, Canada. Four categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…The global recommendation is exclusive HM feeding for 6 months, 1 but a separate analysis of Study B data showed that this practice was frequently compromised after 4 months by introduction of solids and non-formula fluids. 31 We therefore assessed non-exclusive HM feeding to both 4 and 6 months in order to examine associations with and without the influence of complementary feeding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The global recommendation is exclusive HM feeding for 6 months, 1 but a separate analysis of Study B data showed that this practice was frequently compromised after 4 months by introduction of solids and non-formula fluids. 31 We therefore assessed non-exclusive HM feeding to both 4 and 6 months in order to examine associations with and without the influence of complementary feeding.…”
Section: Methodsmentioning
confidence: 99%
“…Outcome measures were: (i) cessation of any HM feeding before 6 months postpartum; (ii) non-exclusive HM feeding postdischarge to 4 months postpartum and (iii) non-exclusive HM feeding postdischarge to 6 months postpartum. The global recommendation is exclusive HM feeding for 6 months,1 but a separate analysis of Study B data showed that this practice was frequently compromised after 4 months by introduction of solids and non-formula fluids 31. We therefore assessed non-exclusive HM feeding to both 4 and 6 months in order to examine associations with and without the influence of complementary feeding.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless, use of this standard indicator is not feasible in a retrospective survey like the CCHS, which captures practices of individuals who gave birth in the previous 5 years. In addition, previous research has shown that infant feeding is not a static process during the first 6 months postpartum and predominant (vs. exclusive) breastfeeding is common (Bodnarchuk et al 2006;Noel-Weiss et al 2012;Mildon et al 2022;Netting et al 2022). Feeding expressed human milk by bottle is also an increasingly common practice in highincome settings (Johns et al 2013).…”
Section: Measuring Breastfeeding Exclusivitymentioning
confidence: 99%
“…Detailed methods for both studies have been reported elsewhere, as have participant demographics and results for breastfeeding metrics (19)(20)(21)(22) . Study A examined the infant feeding practices of clients enrolled at the 5Ps CPNP site, which also implements a postpartum lactation support programme through additional charitable funds from The Sprott Foundation (19) .…”
Section: Study Setting and Participantsmentioning
confidence: 99%